Developing an Agro-Ecological Zoning Model for Tumbleweed (Salsola kali), as Energy Crop in Drylands of Argentina - Falasca, Silvia (2016)
Salsola kali is considered extremely valuable as an energy crop worldwide because it adapts easily to environments with strong abiotic stresses (hydric, saline and alkaline) and produces large amounts of biomass in drylands. This species is categorized as an important weed in Argentina. The aim of this work was to design an agro-ecological zoning model for tumbleweed in Argentina, employing a Geography Information System. Based on the bioclimatic requirements for the species and the climatic data for Argentina (1981–2010 period), an agro-climatic suitability map was drawn. This map was superimposed on the saline and alkaline soil maps delineated by the Food and Agriculture Organization for dry climates, generating the agro-ecological zoning on a scale of 1 : 500 000. This zoning revealed very suitable and suitable cultivation areas on halomorphic soils. The potential growing areas extend from N of the Salta province (approximately 22° S) to the Santa Cruz province (50° S). The use of tumbleweed on halomorphic soils under semi-arid to arid conditions, for the dual purpose of forage use and source of lignocellulosic material for bioenergy, could improve agricultural productivity in these lands. Furthermore, it could also contribute to their environmental sustainability, since the species can be used to reclaim saline soils over the years. Based on international bibliography, the authors outlined an agro-ecological zoning model. This model may be applied to any part of the world, using the agro-ecological limits presented here.